Երիտասարդությունը, տեղի ինքնությունները և սոցիալական տարածության կառուցվածքները հետխորհրդային հայաստանյան գյուղական համայնքներում - Վերմիշյան Հարություն (Bulletin of Yerevan University G: Economics, 2017)
After the collapse of the Soviet Union and the “importation” of democratic and liberal ideologies in line with fundamental social and political transformations led to the change in the discourse on the Armenian rural lifestyle, in the place identities and in self-governing systems. Reform, directed to the development of self-government system in the Post-Soviet Armenia, the social programs meaning to overcome the social issues of the Armenian rural communities, formed a new geopolitical situation, that simultaneously tremendously changing local realities of rurality. Social problems linked to land use, family welfare, migration, place attachment and attraction with urban lifestyles have been actual up to present day, especially among the young people. Observation of place identity as a locally and spatially conditioned phenomenon is common presently in the study of social issues of local communities. According to contemporary sociological approaches, place identity has social prefixes and is reflexive towards social space. The aim of the research is to reveal the changes in place identity and place attachment features within the Armenian rural communities through examination of youth’s perceptions around the rural lifestyle. Relying on secondary analysis of the research data, in-depth interviews among villagers and focus group discussions (8 FGD among village youth) the paper discusses the dynamic interrelation of place identity, social space structures and changing social practices in the Armenian rural communities.